Document Validation by a Notary as a Fiduciary-Based Credit Risk Mitigation - Setiawaty, Dewi; Mashdurohatun, Anis (Jurnal Konstatering, 2026)
This study aims to analyze in depth the role of Notaries in validating documents in the credit granting process with fiduciary guarantees as a form of legal and credit risk mitigation at Bank Perekonomian Rakyat Lingga Sejahtera Pangkalan Bun. The background of the study is based on the frequent problems found in credit practices, including incomplete debtor identities, inconsistencies in collateral data, failure to transfer ownership, and weak understanding of the debtors regarding the legal consequences of fiduciary agreements. These conditions have the potential to cause disputes at the execution stage and weaken the bank's preferred position as a creditor. The research method used is an empirical juridical approach with analytical descriptive specifications. Primary data were obtained through in-depth interviews with Notary partners, credit analysts, and the BPR legal department, while secondary data were obtained from laws and regulations, notarial law literature, and relevant scientific journals. Data analysis was conducted qualitatively with triangulation techniques to ensure the validity of the findings. The results show that Notaries have a central role as a preventative guard in credit risk management. These roles include verifying the identity of legal subjects, examining the legality and validity of collateral objects, preparing credit agreements and fiduciary guarantee deeds that meet formal and material requirements, and implementing fiduciary registration through the Ministry of Law and Human Rights' electronic system. Strict validation has been proven to prevent duplicate objects, reduce the potential for non-performing loans, and strengthen the bank's executorial position following the Constitutional Court's ruling on fiduciary execution mechanisms. The study also found several obstacles, namely low legal literacy of MSME debtors, differences in physical and administrative vehicle data, disruptions to the electronic registration system, and differences in interpretation of execution clauses between banks and Notaries. To overcome these obstacles, integrated validation operational standards, intensive coordination between banks and Notaries, integration of ownership databases, and increased legal education for debtors are needed. The study concluded that the quality of Notary validation is directly proportional to the effectiveness of fiduciary-based credit risk mitigation.